2018
DOI: 10.1103/physrevmaterials.2.064604
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and quantum mobility of modern GaAs/AlGaAs heterostructures

Abstract: In modern GaAs/AlxGa1−xAs heterostructures with record high mobilities, a two-dimensional electron gas (2DEG) in a quantum well is provided by two remote donor δ-layers placed on both sides of the well. Each δ-layer is located within a narrow GaAs well, flanked by narrow AlAs layers which capture excess electrons from donors. We show that each excess electron is localized in a compact dipole atom with the nearest donor. Nevertheless, excess electrons screen both the remote donors and background impurities. Whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 63 publications
6
45
0
3
Order By: Relevance
“…This is in reasonable agreement with N 1 /N 2 ∼ 10 obtained previously in Ref. 12 from the analysis of mobility and quantum mobility of an ultrahigh mobility sample of similar design. As mentioned in Ref.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…This is in reasonable agreement with N 1 /N 2 ∼ 10 obtained previously in Ref. 12 from the analysis of mobility and quantum mobility of an ultrahigh mobility sample of similar design. As mentioned in Ref.…”
supporting
confidence: 93%
“…These oscillations can be substantially reduced due to fluctuations of charge density of the remote doping layers, which induce fluctuations ∆ν of the 2DEG filling factor around half integer ν. To estimate ∆ν we used results of numerical modelling of doping layers of modern GaAs/AlGaAs devices [18], which showed that in the ground state of localized excess electrons of the doping layers with fraction of filled donors f ≃ 0.5, the mean square fluctuation of charge of the square of size L around average value is ∼ 1e practically independent on L. Then in area Λ 2 one has ∆ν ≃ 2 1/2 2πl 2 B /Λ 2 ≃ 1/(2N + 1), where the factor 2 1/2 results from the addition of mean square fluctuations of the two doping layers. Such fluctuations produce fluctuations of the width of filled and empty stripes ∆Λ ≃ 1.42R c /(2N + 1), which reduce the amplitude of oscillations of b 1,2 (N ) at least twice and allow us to use their average values b 1 = 7.5 × 10 −4 and b 2 = 8.9 × 10 −2 .…”
mentioning
confidence: 99%
“…Thick boundaries mark destruction of stripe phases where Γi ∼ Γs. Nq andσq are given by Eqs (13). and(14), respectively.…”
mentioning
confidence: 99%
“…Since the quantum scattering rate, in general, is much more sensitive to remote impurities than the transport scattering rate, we can conclude that illumination primarily affects scattering from remote impurities rather than from those in the vicinity of the GaAs quantum well. Insensitivity of τ to illumination then suggests that contribution of the remote impurities to the momentum relaxation rate is negligible even before the illumination, i.e., that τ is limited by scattering from unintentional background impurities within the GaAs quantum well and in the AlGaAs barriers [12,35]. The quantum scattering rate, on the other hand, can still contain a sizable or even dominant contribution from the remote impurities, e.g.…”
Section: 32]mentioning
confidence: 99%
“…Recent theoretical examination [12,35] of the doping layers has shown that excess electrons which occupy the X-bands of the AlAs mini-wells form compact dipoles with donors of their choice (to minimize their energy) which reside in GaAs mini-wells. These X-electrons can effectively screen the random potential from the remaining un-paired ionized Si atoms and the screening effectiveness grows rapidly with their number.…”
Section: 32]mentioning
confidence: 99%